Laboratory Modeling of Coeval Brittle and Ductile Deformation During Magma Emplacement Into Viscoelastic Rocks - Bertelsen, Håvard Svanes; Rogers, Benjamin D.; Galland, Olivier; Dumazer, Guillaume; Abbana Benanni, Alexandre (Frontiers in Earth Science, 2018)
The mechanics of magma emplacement in the Earth's crust corresponds to the flow of a viscous fluid into a deforming solid. The Earth's crust through which magma is emplaced is visco-elasto-plastic, and field observations show that most intrusions are likely to be accommodated by combined brittle and ductile deformation of their host. However, mechanical models of magma emplacement account for either purely elastic, plastic or viscous end-member rheology of the host rock, therefore they cannot simulate the natural diversity of magma intrusion shapes and magma emplacement mechanisms. Thus they are of limited use to predict under which conditions intrusions of contrasting shapes form. Here we present a series of 2D experiments where a viscous fluid (oil) was injected into a host matrix (laponite gel), the visco-elasto-plastic rheology of which is varied from dominantly viscous to dominantly elastic. The oil intrusion in the elastic gel is a thin conduit with a sharp tip, like magmatic dykes, whereas the oil intrusion in the viscous gel is rounded, like diapirs. In addition, the oil intrusion exhibits complex, hybrid shapes. The experiments were run in a polariscope, which highlighted birefringence patterns related to deformation structures within the gel. Our experiments show a strong correlation between intrusion shapes and host matrix deformation modes: (1) thin intrusions dominantly propagate by tensile failure and elastic deformation of the host, (2) rounded "diapiric" intrusions dominantly propagate by viscous flow of the host, and (3) irregular "hybrid" intrusions propagate by coeval brittle (tensile and shear) and ductile deformation of the host. Our novel experiments are the first able to produce the natural diversity of intrusion shapes and host deformation mechanisms. In addition, our results show that the use of a polariscope in gel experiments is essential to unravel the mechanics of magma emplacement within a host of realistic visco-elasto-plastic rheology.